2021
DOI: 10.3390/jmse9121347
|View full text |Cite
|
Sign up to set email alerts
|

Deriving the 100-Year Total Water Level around the Coast of Corsica by Combining Trivariate Extreme Value Analysis and Coastal Hydrodynamic Models

Abstract: As low-lying coastal areas can be impacted by flooding caused by dynamic components that are dependent on each other (wind, waves, water levels—tide, atmospheric surge, currents), the analysis of the return period of a single component is not representative of the return period of the total water level at the coast. It is important to assess a joint return period of all the components. Based on a semiparametric multivariate extreme value analysis, we determined the joint probabilities that significant wave hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…Based on the high-order spectral (HOS) numerical model, both the Bragg resonance characteristics that were induced by the regular waves and random waves were investigated. With regular waves, the study showed that the wave-focusing effect is related to the angle of the V-shaped undulating bottom and that the optimal angle of inclination for the V-shaped undulating bottom is 162.24 • To derive the 100-year total water level around the coast of Corsica by combining trivariate extreme value analysis and coastal hydrodynamic models, Louisor et al [4] focused on providing extreme scenarios through which wind wave and coastal hydrodynamic models, i.e., SWAN and SWASH-2DH, could be populated in order to compute the 100-year total water level (100y-TWL) along the coasts. They showed how the proposed multivariate extreme value analysis can help to more accurately define low-lying zones that are potentially exposed to coastal flooding, especially in Corsica, where a unique value of 2 m was taken into account in previous studies.…”
Section: Details Of Papersmentioning
confidence: 99%
“…Based on the high-order spectral (HOS) numerical model, both the Bragg resonance characteristics that were induced by the regular waves and random waves were investigated. With regular waves, the study showed that the wave-focusing effect is related to the angle of the V-shaped undulating bottom and that the optimal angle of inclination for the V-shaped undulating bottom is 162.24 • To derive the 100-year total water level around the coast of Corsica by combining trivariate extreme value analysis and coastal hydrodynamic models, Louisor et al [4] focused on providing extreme scenarios through which wind wave and coastal hydrodynamic models, i.e., SWAN and SWASH-2DH, could be populated in order to compute the 100-year total water level (100y-TWL) along the coasts. They showed how the proposed multivariate extreme value analysis can help to more accurately define low-lying zones that are potentially exposed to coastal flooding, especially in Corsica, where a unique value of 2 m was taken into account in previous studies.…”
Section: Details Of Papersmentioning
confidence: 99%
“…Un tema de impacto para poblaciones y autoridades de todo el mundo es la erosión que se presenta en los acantilados costeros (Conforti et al, 2014;De la Peña & Sánchez, 2018;López & Vidal, 2012;Ordoqui & Hernández, 2009;Del Río & Gracia 2014) y la pérdida de terrenos montañosos (Milheiro, 2007), varios son los factores que influyen en la vulnerabilidad de las zonas costeras (Azuz et al, 2020;Merlotto et al, 2017;Ricaurte et al, 2021), considerándose como detonante a la intensidad y frecuencia de las precipitaciones (Bezerra et al, 2011;Kyprioti et al, 2021;Lemke & Miller, 2021;Useros, 2013). , y aumento acelerado del nivel del mar (Evelpidou et al, 2021;Louisor et al, 2021;Silveira et al, 2021;Wu et al, 2002). En el mundo más del 37% de la población vive dentro de los 100 km de la costa, siendo el 80% de estas, costas rocosas (Brambati, 2004;Cuervas et al, 2021;Emery & Kuhn, 1982;Rangel & Posada, 2013;Sunamura, 1993;Violante, 2009), las zonas de acantilados se encuentran en el 52% de las zonas costeras a nivel global (Gómez & Pérez, 2021), se erosionan, amenazando con frecuencia a las comunidades costeras (Bruno et al, 2021;Coca et al, 2019;Mineo et al, 2018;Stephens et al, 2021), la infraestructura (Andreadis et al, 2021;Pappalardo et al, 2016) y los sitios históricos en todo el mundo (Fanti et al, 2013;Young & Ashford, 2008).…”
Section: Introductionunclassified